Emotional availability: theory, research, and intervention - Saunders, Hannah; Kraus, Allyson; Barone, Lavinia; Biringen, Zeynep (Frontiers in Psychology, 2015)
Attachment Theory (Bowlby, 1969) and its limitations are first described. Next, emotional availability (EA; Biringen, Robinson, & Emde, 1998; Biringen, 2008) is introduced as an expansion upon the original conceptualization of the parent-child attachment relationship. As a construct and as a measure, EA considers the dyadic and emotional qualities of adult-child relationships. EA is predictive of a variety of child outcomes, such as attachment security, emotion regulation, and school readiness. Recently developed programs to enhance adult-child emotional availability are described.